COOPERATION MODELS IN THE WESTERN BALKANS AS DETERMINANTS OF REGIONAL INTEGRATION (Heritage, 2025)
Regional integration is taking an increasingly important place in contemporary international relations and it is necessary to analyze it from two angles: 1 - as a political, economic and security entity that significantly determines the positioning of political entities of a certain region on the stage of international relations; 2 - as a political, economic and security entity that provides opportunities and capacities for dealing with contemporary and ongoing challenges, risks and threats. The main research question is to what extent regional cooperation in the Western Balkans determines the sustainability of the entities that are part of the regional environment in question. The goal is to prove the thesis that regional cooperation, coordination and integration in the Western Balkans, with absolute respect for the national interests of political entities, is an imperative in contemporary international relations, in the processes of dealing with contemporary challenges, risks and threats, but also in the comprehensive process of creating sustainability, both at the regional and national levels.
Keywords: Western Balkans, regional integration, Berlin Process, Open Balkans, CEFTA, digitalization, neoclassical realism